Pengaruh Komitmen Organisasi Terhadap Kinerja Karyawan(Studi Pada PT. GO-JEK Cabang Solo) - Setyawati, Devi, Muzakar Isa., SE., M.Si (2017)
This study aims to determine the effect of affective commitment, continuous commitment, and normative to the performance of employees of PT. GO-JEK. Based on the results of this study is expected to provide input to the PT.GO-JEK to look for new ways that increasingly improve the efficiency and effectiveness of the organization or company as a whole that can improve employee performance. Hypothesis testing in this research using moderating regression analysis tool with t test, F test and coefficient of determination (R2). The population in this study amounted to 100 people who are employees of PT.GO-JEK in Solo area. The sample used in this study is total sampling, which takes the entire sample population so that the total sample amounted to 100 employees of PT. GO-JEK. Based on the results of the study note that Affective commitment significantly influence the performance of employees of PT. GO-JEK Solo Branch, this shows that any increase in affective commitment, it will improve the performance of employees of PT. GO-JEK Solo Branch. Continuance commitment has significant effect on employee performance of PT. GO-JEK Solo Branch, it shows that every increase continuance commitment, it will improve the performance of employees of PT. GO-JEK Solo Branch. Normative commitment significant effect on employee performance of PT. GO-JEK Solo Branch, this shows that any increase in normative commitment, it will improve the performance of employees of PT. GO-JEK Solo Branch.